PENGARUH UKURAN PARTIKEL DAN KOMPOSISI TERHADAP SIFAT KEKUATAN BENTUR KOMPOSIT EPOKSI BERPENGISI SERAT DAUN NANAS - Syahrinal Anggi Daulay; Fachry Wirathama; Halimatuddahliana (Jurnal Teknik Kimia USU, 2014)
This research was aimed to investigate the effect of pineapple leafs particle size and pineapple leaf fiber composition of the impact strength of epoxy composites filled with pineapple leaf fibers. The composites were made by hand lay up method by mixing epoxy and pineapple leaf fiber with particle size variation of 30 mesh, 40 mesh, 70 mesh, 100 mesh, and volume fraction ratio between filler and matrix 5/95, 10/90, 15/85 (v/v). Mechanical properties wich tested was impact strength and supported with SEM analysis. The results obtained show that the addition pineapple leaf fiber as filler in epoxy composites generally increase the impact strength of the composites, with best performance shown by 100 mesh particle size variation with ratio 90/10 (v/v) which from SEM analysis show that this variation having better filler distribution.